Electromagnetic field energy and radiation intensity in a medium with temporal and spatial dispersion outside the transparency domain - Trigger, S.A.; Zagorodny, A.G. (Вопросы атомной науки и техники, 2018)
Calculation of electromagnetic field energy in a medium with temporal and spatial dispersion outside the
transparency domain is discussed. It is shown that charged particle contribution to the energy of electromagnetic
perturbations in the general case can be described in terms of a bilinear combination of the dielectric polarizability
of the medium. The explicit form of such contribution is found. The relations obtained are used to generalize the
Planck law and Kirchhoff law to the case of an absorptive medium with spatial dispersion. Розраховано енергію електромагнітного поля в середовищі з часовою та просторовою дисперсіями поза
областю прозорості. Показано, що в загальному випадку внесок енергії частинок середовища в енергію
електромагнітного збурення описується в термінах білінійних комбінацій діелектричної поляризованості
середовища. Знайдено явний вигляд такого внеску. Отримані результати використано для узагальнення закону
Планка і закону Кірхгофа для поглинального середовища з просторовою дисперсією. Рассчитаны энергии электромагнитного поля в среде с временной и пространственной дисперсиями вне
области прозрачности. Показано, что в общем случае вклад энергии частиц среды в энергию электромагнитного
возмущения описывается в терминах билинейных комбинаций диэлектрической поляризуемости среды. Найден
явный вид такого вклада. Полученные результаты использованы для обобщения закона Планка и закона
Кирхгофа для поглощающей среды с пространственной дисперсией.